Organizational Citizenship Behavior in the People's Republic of China - Farh, Jiing-Lih; Zhong, Chen-Bo; Organ, Dennis W. (Organization Science, 2004)
In recent years, Western scholars have increasingly emphasized the importance of organizational citizenship behavior (OCB)—employees' behavior and actions that are not specifically designated in their formal job duties. Almost the entire body of empirical research on OCB is based on studies conducted in the United States, using U.S. employee populations as samples. Taking an inductive approach, we examined forms of OCB in the People's Republic of China (China). From a diverse sample of 158 employees and managers in 72 state-owned, collective, town and village, foreign-invested, and private enterprises in China, we collected 726 OCB incidents or items that were commonly observed in the workplace. We then subjected these to a content analysis to identify major forms of OCB. Results of our analysis revealed 10 dimensions of OCB, with at least one dimension not evident at all in the Western literature, and four that do not figure importantly in established OCB measures. The type of Organizations influenced the reporting of several forms of OCB. Results suggested that Chinese formulation of OCB differs from that in the West, and is embedded in its unique social and cultural context. We discuss these results in terms of their implications for future research in OCB.